Corrosion Inhibition of Sodium Silicate with Nanosilica as Coating in Pre-Corroded Steel - Marish S. Madlangbayan; Carlo Nico B. Diola; Alvin Karlo G. Tapia; Milagros M. Peralta; Engelbert K. Peralta; Ronaniel A. Almeda; Maris Asuncion L. Bayhon; Marloe B. Sundo (Civil Engineering Journal, 2021)
This study was conducted to investigate the potential of using sodium silicate with nanosilica as a treatment to inhibit the progress of corrosion in steel specimens that are already corroded. Steel specimens measuring 16 mm in diameter and 4 mm in thickness were prepared and subjected to pre-corrosion by immersion to 3.5% NaCl solution. Two sets of specimens were then dip-coated with sodium silicate containing nanosilica. One set was coated with 1% nanosilica, and the other was coated with 2.5% nanosilica. The coated specimens were then subjected to Complex Impedance Spectroscopy (CIS) at 20 Hz to 20 MHz frequency range. Compared with the sodium silicate coating with 1% nanosilica, the sodium silicate coating with 2.5% nanosilica had a larger semi-circle curve in the Nyquist plot. Similarly, the sodium silicate coating with 2.5% nanosilica also showed larger magnitudes of impedance at the low-frequency region and larger phase angles at the high-frequency regions in the Bode plot. These results imply that the sodium silicate coating with 2.5% nanosilica coating demonstrated better capacitive behavior. In addition, equivalent circuit modelling results also showed that the sodium silicate coating with 2.5% nanosilica had higher coating resistance and lower coating capacitance as compared to the sodium silicate coating with 1% nanosilica. Doi: 10.28991/cej-2021-03091761 Full Text: PDF